The IDENTIFICATION OF EARLY WARNING SIGNS IN PATIENTS AT RISK OF ACUTE RESPIRATORY EMERGENCIES: IDENTIFICATION OF EARLY WARNING SIGNS IN PATIENTS AT RISK OF ACUTE RESPIRATORY EMERGENCIES - Hasibuan, Ira Astuti (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Early identification of warning signs is the key to preventing further complications and reducing the death rate due to this condition. This study aims to identify early warning signs in patients at risk of cardiovascular emergencies and analyze the relationship between cardiovascular risk factors and the appearance of clinical symptoms that can predict the occurrence of emergencies. In this study, an analysis was carried out on 200 patients with cardiovascular risk factors, such as hypertension, diabetes, obesity, and a family history of heart disease, who came to the emergency department. The results of the study showed that some of the most common early warning signs found in patients included chest pain (58%), shortness of breath (45%), extreme fatigue (38%), palpitations or irregular heartbeat (30%), swelling of the legs (22%), and dizziness or fainting (18%). The risk factors of hypertension, diabetes and obesity were found to be significantly associated with the appearance of these symptoms. This research emphasizes the importance of early recognition and treatment of these warning signs to prevent further complications, such as heart attacks or acute heart failure, which can be fatal. Better early detection through patient and medical personnel education can improve the prognosis and quality of life of patients at risk of cardiovascular emergencies.